Bot Day 2016, San Francisco, CA. (O'Reilly, 2016)
"Bots--conversational interfaces driven by artificial intelligence--are revolutionizing the way we interact with computers, online services, and each other. The public has accepted Siri and Google Talk. Alexa, Amazon's countertop voice bot that listens and helps you with your everyday chores, is primed for holiday sales. Bot Day 2016, O'Reilly Media's first-ever conference on bots, presented some of the visionaries responsible for creating the new bot world. This video compilation offers complete access to every presentation delivered at the event. Lili Cheng (Microsoft Research FUSE Labs), Andy Mauro (Automat), Peter Skomoroch (Skipflag), Cathy Pearl (Sensely), Amir Shevat (Slack), and Joshua Browder (DoNotPay) provide overviews of the technical concerns of bot-making, while VCs like Benedict Evans (Andreessen Horowitz), Momin Mirza (Verizon), and Ping Li (Accel Partners) review the strategic outlook for the emerging bot industry. Watching this video will give you a deeper understanding of bot making, bot investing, and the reasons why Microsoft CEO Satya Nadella says 'bots are the new apps.'"--Resource description page.